The Corporate Social Responsibility is just a twist in a Möbius strip - Nazaria Solferino; Viviana Solferino (Kiel Institute for the World Economy (IfW), 2016)
In recent years economics agents and systems have become more and more interacting and juxtaposed, therefore the social sciences need to rely on the studies of physical sciences to analyze this complexity in the relationships. According to this point of view the authors rely on the geometrical model of the Möbius strip used in the electromagnetism which analyzes the moves of the electrons that produce energy. They use a similar model in a Corporate Social Responsibility context to devise a new cost function in order to take into account of three positive crossed effects on the efficiency: i) cooperation among stakeholders in the same sector; ii) cooperation among similar stakeholders in different sectors and iii) the stakeholders' loyalty towards the company. By applying this new cost function to a firm's decisional problem the authors find that investing in Corporate Social Responsibility activities is ever convenient depending on the number of sectors, the stakeholders' sensitivity to these investments and the decay rate to alienation. The work suggests a new method of analysis which should be developed not only at a theoretical but also at an empirical level.
Keywords: L13; C21; Z1; 330; corporate social responsibility; econophysics; firm behavior